Extramedullary Acute Myeloid Leukemia: Leukemic Pleural Effusion, Case Report and Review of the Literature - Pemmaraju, Naveen; Chang, Elaine; Daver, Naval; Patel, Keyur; Jorgensen, Jeffrey; Sabloff, Bradley; Verstovsek, Srdan; Borthakur, Gautam (Frontiers in Oncology, 2014)
Objective and Importance: Malignant pleural effusions occur in the setting of both solid and hematologic malignancies. Pleural effusion caused by leukemic infiltration is an unusual extramedullary manifestation of acute myeloid leukemia (AML) with fewer than 20 cases reported.1-11 We report a case of pericardial and pleural effusions in a patient with AML and review the literature. Clinical presentation: In this case, a 55 year old man with previous history of myeloproliferative neoplasm (MPN) experienced transformation AML, heralded by appearance of leukemic pleural effusions. The patient was identified to have leukemic pleural effusion based upon extended cytogenetic analysis of the pleural fluid, as morphologic analysis alone was insufficient. Intervention: The patient was treated with hypomethylator-based and intensive chemotherapy strategies, both of which maintained resolution of the effusions in the remission setting. Conclusion: Due to the rarity of diagnosis of leukemic pleural effusions, both cytogenetic and fluorescence in situ hybridization (FISH) testing are recommended. Futhermore, systemic chemotherapy directed at the AML can lead to complete resolution of leukemic pleural effusions. Objective and Importance Pleural effusion caused by leukemic infiltration is an unusual extramedullary manifestation of acute myeloid leukemia (AML), but may be more common than previously thought. Fewer than 20 cases have been reported.1-11 We report a case of pericardial and pleural effusions in a patient with AML and review the literature.